Investigating the efficacy of mineralocorticoid receptor antagonists for cardiovascular outcomes in different diseases - Jiao Wang; Meijuan Zheng; Yuchun Yang; Lei Zhang; Muhuyati Wulasihan (ESC Heart Failure)
Abstract Aims Mineralocorticoid receptor antagonists (MRAs) are crucial in managing cardiovascular diseases, with different MRAs demonstrating varying efficacy across diverse disease contexts. This research aims to compare the cardiovascular protective effects of different MRAs across various disease conditions. Methods Evidence from eligible randomized controlled trials (RCTs), cohort studies, or real‐world registry studies that investigated hazard ratio (HR) with 95% confidence intervals (CIs) of major adverse cardiovascular events (MACE) following MRA treatment were searched in four literature databases. Surface under the cumulative ranking curve values were calculated. Sensitivity analyses were conducted to assess the robustness of the findings. Results Data from a total of 21 investigations involving 61 076 participants were included. The control groups comprised placebo arms in RCTs and non‐MRA users in observational studies. In heart failure (HF) patients, finerenone showed highest efficacy with HR 0.68 (95% CI 0.47–0.95) versus control, followed by spironolactone (HR 0.72, 95% CI 0.55–0.89) and eplerenone (HR 0.81, 95% CI 0.64–1.10). For non‐HF populations, spironolactone showed the most protective effect (HR 0.40, 95% CI 0.15–1.10), followed by eplerenone (HR 0.58, 95% CI 0.25–1.30) and finerenone (HR 0.89, 95% CI 0.50–1.60). In diabetes mellitus population, spironolactone maintained advantage (HR 0.57, 95% CI 0.13–2.43) in contrast to finerenone (HR 0.74, 95% CI 0.41–1.25) and eplerenone (HR 0.78, 95% CI 0.40–1.62). Sensitivity analyses which excluded observational studies and included only RCTs showed consistent results for these disease populations. But the chronic kidney disease/end‐stage renal disease population exhibited different patterns: eplerenone showed optimal efficacy in primary analysis (HR 0.62, 95% CI 0.32–1.20) followed by spironolactone (HR 0.79, 95% CI 0.49–1.06) and finerenone (HR 0.87, 95% CI 0.55–1.35). Sensitivity analysis revealed better result for spironolactone in this population (HR 0.40, 0.15–1.10) followed by eplerenone (HR 0.62, 0.27–1.40) and finerenone (HR 0.87, 0.49–1.50). Conclusions MRAs exhibit varying cardiovascular protective effects depending on the disease context. These findings support tailored treatment strategies based on specific disease conditions to optimize patient outcomes. Further research with larger and more diverse datasets is needed to validate these results and inform clinical decision‐making.